Avaliação ambiental dos processos construtivos de estrutura metálica e pré-moldada de concreto por meio de análise do ciclo de vida - Mantovani, F.; Sebastiany, L. D.; Christ, R.; Mancio, M. (Revista ALCONPAT, 2013)
Concerns about the reduced availability of natural resources and the increased degradation ofthe environment have stimulated the appearance of new techniques which can help companiesto implement a more environmentally sustainable production model. Because of that, newtechnologies and environmentally friendly materials have been developed, such as assessmentsystems and tools to support decision-making early on, during the design process. Life cycleanalysis (LCA) emerges as a powerful tool for analyzing and choosing alternatives from anenvironmental perspective. This study provides experimental data on the flow of raw materials,products and waste, on the production process of a precast concrete column and a steel column.To make this analysis, the GaBi software was used. Results show that the steel column hasgreater environmental impact when compared with a reinforced concrete alternative.Keywords: Life cycle analysis; precast concrete structures; steel structures.